(3MGTjI eMj GdOjf GdJGdTj Ydi TQM EjSGZhLj dMSGe GdOjf GdcGJjs - (3GdJGdTj, eMjj GdOjfs ((3eOQSI fUQ Gddg bGVs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bGd GdMeO ddg GdhGLH hLhOg GdeeJfY fXjQg Cbhd CaJJM cJGHg HGdMeO HYO GdGHJOGA HGdHSedI dCf COGA GdhGLH Yf TcQ fYeGFg s
(3BNQgG (B:s
(3hGdMS hgh eJMjR hcd eG gh eTGgOI jOQc HGdeTGgOI hGdMS eJMjR acd ehLhO eJMjR hGdZQV ef GdeZGdWI JZdjW GdNUe hOaYgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B1 / 207s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs